Laundry Dash / Brenda Charmine Joid ... [et al.] - Joid, Brenda Charmine; Junne, Carlvett Ellene; Ruaisan @ Ruisen, Juneanna; Noh, Nazira; Ahmad, Faridah (2016)
Laundry Dash is a business of laundry with cafe that will started on 14/March/2016. This business is owned and operated by Brenda Charmine, Carlvett Ellenne, Faridah, Juneanna and Nazira as are business partner. This form of business is partnership business. The main services of our business is providing laundry services that consist of several package such as self serve laundry services, drop off laundry services and dry cleaning. We also providing additional services such cafe services and free Wi-Fi provided to all customers. The business location is situated at D-G-30, Jalan Tun Fuad Stephens, 88000 Kota Kinabalu Sabah. We choose this location because it is a great potential for this business as it is situated near with some of the university and students that preferred to go to our laundry. For the residential it refer to the peoples that lives near to our laundry. This location also centres of working area and community even though there is a bit competitor in this area. But in forming this business we already prepare physical, mental and emotion to face any risks that will come in the future. We believe that our business have potential in this millennium especially in urban area because people are busy with studies and work. As the consequences they have limited time to do house chores like washing cloth. Furthermore, our ways of thinking has changed people no longer assume that laundry is only necessary for wealth society. Therefore, they prefer to send their clothes to the nearest laundry shop. In addition, our laundry also have uniqueness whereby we provide a cafe services that we assuming can attract customers because while waiting for their laundry finish, they can enjoy a foods and free Wi-Fi services. As a new entrepreneur, we choose this service business because this kind of business does not require large capital and professional workers. In preparation of this business plan, we hope that in the future we can make this business success and survive even though there will be many competitions in other business field.